Hair Mercury Concentrations among Residents Living Near Artisanal and Small-Scale Gold Mining Activities in Indonesia - Rini Maya Sari; Muhammad Irsan; Legiran Legiran; Poedji Loekitowati Hariani; Lia Nurbanillah Fujianti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Mercury use in artisanal and small-scale gold mining (ASGM) remains a major public health concern in Indonesia. This cross-sectional biomonitoring study examined the factors associated with mercury exposure among 50 adults living near ASGM activities in the Bungo District. The interview data covered sociodemographic, occupational, behavioral, and exposure-related factors, while hair mercury concentrations were measured using inductively coupled plasma mass spectrometry. Descriptive analyses, bivariate logistic screening, and multivariable logistic regression with backward stepwise selection were performed. In the final model, non-mining participants had lower odds of higher mercury exposure than mining-related workers (OR = 0.164; 95% CI: 0.030–0.892; P = 0.036). Adults aged ≥45 years had lower odds than those aged 21–44 years (OR = 0.097; 95% CI: 0.020–0.474; p = 0.004), whereas women had higher odds than men (OR = 8.032; 95% CI: 1.586–40.675; p = 0.012). The model showed moderate explanatory performance (Nagelkerke R² = 0.414) and 78.0% accuracy. These findings indicate higher exposure among younger adults, women, and mining-related workers, supporting targeted biomonitoring, occupational risk reduction, and community-based interventions in areas affected by ASGM.